Mineral phase equilibria and zircon geochronology constrain multiple metamorphic events of high‐pressure pelitic granulites in south‐eastern Tibetan Plateau. (11th March 2019) - Ji, Lei; Liu, Fulai; Wang, Fang; Santosh, M.; Tian, Zhonghua; Sun, Zaibo
Abstract : The Ailao Shan (ALS) metamorphic belt separates the Indochina Block to the west from the South China Block and is an important region for understanding the history of evolution of the Palaeo‐Tethys in relation to the collision of the Indian and Eurasian plates and the formation of the Tibetan Plateau. The multiple metamorphic events and P–T–t paths of the ALS belt remain debated. Here, we present the results of an integrated study of the petrography, mineral chemistry, phase equilibria modelling, and zircon U–Pb geochronology of high‐grade metasedimentary rocks from this belt. Abundant metamorphic zircon grains with mineral inclusions of Sil/Ky + Bt + Pl + Qz ± Mnz record two metamorphic events, the first one during the Triassic (227–220 Ma), although intense shearing overlapped during the Cenozoic and mineral assemblages of this thermal event were not preserved. The second metamorphic event occurred during the Palaeogene (49 –23 Ma) and involved three stages: (a) a peak high‐pressure (HP) granulite‐facies metamorphism (M1 ) with a mineral assemblage of Ky + Grt1 + Bt1 + Pl + Qz ± Kfs; (b) a postpeak near‐isothermal decompression (M2 ) characterized by Sil1–2 + Grt2 + Bt1 + Pl + Qz + Kfs + Ilm and the decompression reactions of Grt + Ky + Qz = 3An and Ky = Sil; and (c) a late decompressional cooling (M3 ) with a mineral assemblage of Sil3 + Grt3 + Bt2 + Pl + Qz + Mnz ± Kfs, followed by a series of hydration reactions. The metamorphic evolution occurred along a clockwise P–T–t path with peak P–T conditions of 13.5–14.0 kbar and 810–820°C. Our new data, combined with those from previous studies, reveal that the Diancang Shan–Ailao Shan Complex Belt is not a single suture that represents the closure of the Palaeo‐Tethyan Ocean during the Triassic, but that it also represents a typical continent–continent collisional orogenic belt that formed during the Eocene–Oligocene prior to the strong left‐lateral, ductile deformation along the Ailao Shan–Red River shear zone.